Evidence on language monitoring in primary healthcare: a scoping review - Ivana Vieira de Resende Teixeira; Ana Carolina Andrade Valadares; Stela Maris Aguiar Lemos (CoDAS, 2025)
ABSTRACT Purpose To map scientific productions on language monitoring in primary healthcare. Methods This scoping review was guided by the following research question “What is the evidence of language development in early childhood in primary healthcare surveillance?”. Studies were searched from February to November 2023 in the MEDLINE, LILACS,Cochrane, Scopus, Web of Science, and EMBASE databases. It included original research articles and reviews with no restriction on time or language and excluded samples with suspected or confirmed diagnoses of intellectual disability, hearing loss, and global developmental delays. Two researchers independently screened titles and abstracts and read the full text of the articles. References were managed in Rayyan. Results The search found 436 studies, of which 220 were excluded for being duplicates and 177 for not answering the research question. Hence, 39 articles were read in full text, of which 31 were excluded for not addressing the topic. Eight articles were included in the review (six original research articles and two reviews). The studies collected data from children aged 1 month to 5 years who visited primary care units for vaccinations or consultations, and during home visits. The use of instruments and clinical observation were the strategies used to investigate language development. The prevalence of language delay ranged from 2.5 to 31%. Conclusion Language development is not yet regularly monitored in child health surveillance in primary care.